Examining the efficacy and safety of endobiliary radiofrequency ablation for ingrowth occlusion after metal stent placement using a bovine model. (31st December 2022) - Inoue, Tadahisa; Kutsumi, Hiromu; Ibusuki, Mayu; Yoneda, Masashi
Abstract: Background: Although endobiliary radiofrequency ablation (RFA) may be an option for the treatment of ingrowth occlusion after self-expandable metal stent (SEMS) deployment, its utility remains uncertain. This study aimed to clarify its utility and safety using bovine liver. Methods: A prototype multifunctional RFA catheter and conventional uncovered SEMS were employed in this experimental study. We devised three model types: the ingrowth-ablation, ingrowth-ablation with stent-wire contact (created such that the electrodes were in contact with the metal stent-wire), and standard-ablation models (control). The study outcome was the ablation depth associated with RFA, which was compared among the three models. Results: Thirty-six ablation procedures were conducted (12 for each of the 3 models). In the unipolar mode, the median ablation depth with the stent-wire contact model (1.0 mm) was significantly lower than that of the ingrowth-ablation (2.0 mm, p = 0.005) and standard-ablation models (2.3 mm, p = 0.004). There was no significant difference between the ingrowth-ablation and standard-ablation models ( p = 0.563). In the bipolar mode, the median ablation depth with the stent-wire contact model (1.0 mm) was also significantly lower than that of the ingrowth-ablation (2.1 mm, p = 0.008) and standard-ablation models (2.0 mm, p = 0.011), and there was no significant difference between the ingrowth-ablation and standard-ablation models ( p = 0.807). Scorching around the stent-wire was not observed in any specimen. Conclusions: In this ex vivo study, endobiliary RFA for ingrowth occlusion can be considered a useful modality, but the ablation effect is diminished when the electrode comes into contact with the stent-wire.